Solutions in the social health field for people with advanced chronic diseases associated with aging (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
Social changes are generating new health problems, increasing pathologies of socio-cultural origin (which especially impact older people) and new paradigms appearing in the approach to illness, disability and dependency. Technological advances and new therapeutic processes entail different ways of addressing chronic diseases and, consequently, imply different needs for equipment, infrastructure and spaces. On the other hand, patients and associations that are increasingly trained and informed, with a growing use of information technologies, generate changes in demand and healthcare needs.Assistance in the social and health field can offer a good response to chronic health problems and end-of-life situations.